The Authority of the Ombudsman of the Republic of Indonesia in Handling Maladministration in Public Services: A State Administrative Law Perspective - Daud Renata Candra Ramadan; Indah Sri Utari (Universitas Negeri Semarang, 2026)
The consequence of the welfare state concept requires the government to provide excellent public services for the community. To oversee the implementation and prevent maladministration, the state established the Ombudsman of the Republic of Indonesia through Law Number 37 of 2008. Legal issues that arise in state administration practice are the end product of the Ombudsman's authority in the form of